Toxoplasmosis treatment with diphenyl diselenide in infected mice modulates the activity of purinergic enzymes and reduces inflammation in spleen - Doleski P.H. (2017)
© 2017 Elsevier Inc.Toxoplasma gondii, an intracellular protozoan, may cause chronic infection in the brain tissue of the host inducing a systemic pro-inflammatory profile. Chronic infections can induce numerous physiological changes, such as alterations in the immune and oxidative profiles. Diphenyl diselenide (PhSe)2, an organoselenium compound, has shown antioxidant and immunomodulatory activities in recent studies. So, the aim of this study was to investigate the activity of purinergic enzymes and reactive oxygen species (ROS) in serum and spleen of mice chronically infected by T. gondii, untreated and treated with (PhSe)2. For this experiment, were divided into four groups: Group A (healthy mice), Group B (healthy mice treated with (PhSe)2), Group C (infected mice) and Group D (infected mice treated with (PhSe)2). Group C and group D were infected via oral route with ME49 Toxoplasma gondii strain. Groups B and D were treated subcutaneously with 5 μmol kg−1 of (PhSe)2. Chronic T. gondii infection induced splenomegaly and physiological changes in the spleen and raised histologic inflammatory markers, ROS levels and the activity of purinergic enzymes activity such as NTPDase, 5´nucleotidase and ADA. In serum, the infection increased 5´nucleotidase and ADA activities. (PhSe)2 per se has managed to decrease ROS levels and ADA activity and increase NTPDase and 5´nucleotidase in spleen. In infected mice, treatment with (PhSe)2 reversed splenomegaly, reduced histological inflammatory markers, ROS levels and ADA activity in the spleen. Our results prove that chronic toxoplasmosis can induce splenomegaly, heightens ROS levels and purinergic enzyme activity in mice. These results suggest that (PhSe)2 is a potential therapy for the alterations found in the spleen in chronic T. gondii infection.